Estimation of States and Parameters of a Drift-Flux Model with Unscented Kalman Filter. Issue 6 (2015) - Nikoofard, Amirhossein; Aarsnes, Ulf Jakob F.; Johansen, Tor Arne; Kaasa, Glenn-Ole
Abstract: We present a simplified drift-flux model (DFM) describing a multiphase (gas-liquid) flow during drilling. The DFM uses a specific slip law, without flow-regime predictions, which allows for transition between single and two phase flows. With this model, we design an Unscented Kalman Filter (UKF) for estimation of unmeasured states, production parameters and slip parameters using real time measurements of the bottom-hole pressure and liquid and gas rate at the outlet. The performance is tested against the Extended Kalman Filter (EKF) by using OLGA simulations of typical drilling scenarios. The results show that both UKF and EKF are capable of identifying the production constants of gas from the reservoir into the well, while the UKF has better convergence rate compared with EKF.